Digital Supply Chain Transformation: Implementing Management Accounting and Blockchain to Address Efficiency Challenges - Aini Indrijawati; Mediaty Mediaty; Elsa Dian Febriyanti; Nathania Pratiwi; Siti Nurul Hediyati (Transpublika Publisher, 2025)
This research is motivated by the absence of an integrated understanding regarding the role of management accounting and blockchain technology in improving supply chain efficiency, as most previous research still examines these two aspects separately. Therefore, this research aims to analyze how the implementation of management accounting and blockchain technology can jointly improve supply chain efficiency. The method used is a Systematic Literature Review (SLR) of 15 reputable scientific articles published within the period 2014–2024 and selected based on specific inclusion and exclusion criteria. The analysis results show that management accounting plays an important role in improving supply chain efficiency through the implementation of activity-based costing, performance measurement systems, and budgeting that can enhance cost transparency, resource control, and decision-making quality. Meanwhile, blockchain technology contributes through enhanced real-time data transparency, end-to-end traceability, implementation of smart contracts, and data recording that cannot be manipulated, thereby reducing the risk of fraud, information asymmetry, and transaction costs. The integration between management accounting and blockchain is proven to strengthen cost accuracy, accelerate transaction processes, and support sustainable supply chain practices. This research concludes that the synergy of management accounting and blockchain technology constitutes an effective strategic framework for creating a more efficient, transparent, and resilient supply chain in the digital era.